Effect of chlorpromazine on intact and irradiated aliquot ctdsDNA samples - Abbed, Ali M.; Al-Nimer, Marwan S.M.; ALhamdany, Mohammad A. (Journal of the Faculty of Medicine Baghdad, 2007)
Bagkground:Chlorpromazine is widely used in human medicine in the therapy of schizophrenia, organic psychosis and the manic phase of manic depressive illness. It expressed a selective cytotoxicity and the results of genotoxicity were positive. Objectives: This study is designed to explore the effect of chlorpromazine on irradiated and non irradiated calf thymus double strands DNA (ctdsDNA) molecule. Methods: Aliquots of irradiated (subjected to UVB light) and non-radiated ctdsDNA samples were incubatyed with different concentrations of chlorpromazine. Further series of experiments studied the simultaneous effects of chlorpromazine and UVB light on aliquots of ctdsDNA, The changes in optic densities of ctdsDNA aliquots were mointered and recorded bu UVspectrophotometer at 260 nm. Results: Chlorpromazine exerts dual effects on non-radiated ctdsDNA aliquots represented by hyperchromasia and hypochromasia in regard to its concentration. It potentiates the effect of UVB radiation on ctdsDNA molecules. Its effect is differed in respect to the radiation status. Conclusion: chlorpromazine exerts several effects on aliquot ctdsDNA samples which are related to the nature of DNA molecule as well as to the concentration of chlorpromazine.Also chlorpromazine potentiates the hyperchromasic effect of UVB radiation on aliquot ctdsDNA samples but it produces completely damage of DNA molecule when the aliquot ctdsDNA samples irradiated in presence of chlorpromazine.